Prinsip good governance dan kepuasan masyarakat penerima BLT dengan kualitas pelayanan pemerintah sebagai variabel pemediasi - Aprilia, Miranti; Rofiuddin, Mohammad (Journal of Management and Digital Business, 2023)
This research aims to analyze the influence of good governance principles on the satisfaction of BLT recipients affected by COVID-19 in 2020 in Manggihan Village, which is mediated by the quality of government services. The sample used in this research was 93 respondents. The data collection technique is by distributing questionnaires in the form of questions to BLT recipients. The analysis method uses multiple linear regression. The findings show that accountability, transparency, participation, responsiveness, and justice principles significantly affect service quality. The principles of accountability, responsiveness, justice, and service quality also influence community satisfaction, but transparency and participation do not. Meanwhile, with mediating variables, service quality can mediate the influence of accountability, transparency, participation, responsiveness, and justice principles on community satisfaction.